2021
DOI: 10.21203/rs.3.rs-294624/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary school Year Advisors’ perspectives on their role, responsibilities and training needs for student mental health: Insights from a co-design workshop

Abstract: Anxiety and depression commonly emerge during adolescence and secondary schools are well placed to recognise deteriorations in young people’s mental health. In Australian secondary schools, Year Advisors (or year co-ordinators), have been identified as key teaching staff for assisting students with their mental health and facilitating help-seeking. However, there is little understanding of the responsibilities of this role and the mental health training needs of these educators. In December 2017, 12 secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Secondary schools can enable the early identification of mental illness, [6][7][8][9] as many Australian teachers are the first to identify emotional problems in students and initiate help-seeking [5]. However, many teachers report a lack of skills and confidence in recognizing and responding to students' mental health needs [10,11] and few have received specialized training in this domain [8,12]. Many teachers have reported that additional management of student well-being has led to greater workload and stress [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondary schools can enable the early identification of mental illness, [6][7][8][9] as many Australian teachers are the first to identify emotional problems in students and initiate help-seeking [5]. However, many teachers report a lack of skills and confidence in recognizing and responding to students' mental health needs [10,11] and few have received specialized training in this domain [8,12]. Many teachers have reported that additional management of student well-being has led to greater workload and stress [8,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…BEAM was developed in partnership with a lived experience advisory group of 12 teachers [ 12 ], and the delivery format was adapted from the evidence-based manager-training program HeadCoach [ 23 , 26 ]. HeadCoach is designed to help managers to better understand and support the mental health needs of their staff [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 70-80% of children who utilise mental health programs do so at school (Nadeem et al, 2018). Furthermore, schools in developed countries often have existing policies that align with mental health prevention (O'Dea et al, 2021). Programs that integrate well with existing policies are more likely to be sustainable (Herlitz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%